Effect of hyperoxic recovery on oxidative stress during a simulated cross-country skiing team sprint - Hauser, A.; Zinner, C.; Wehrlin, J. P.; Sperlich, B. (18th Annual Congress of the European College of Sport Sciences ECSS, Barcelona, Spanien, 2014)
Seven well-trained male endurance athletes performed two 3 x 3-min all-out sprint intervals on a double-poling ergometer at simulated moderate altitude (~1800 m). During the 3-min recovery periods between the 3 x 3-min sprints, all athletes inhaled either hyperoxic (FiO2 = 1.00) or hypoxic (FiO2 ~0.165) air in a randomized and single-blind order. The level of ROS was measured prior the warm-up and directly after the exercise protocol, using the free oxygen radical test (FORT) (Callegari, Parma, Italy). The results are expressed as FORT units (FORT U), where one FORT U corresponds to 0.26 mg/L of H2O2. Oxidative stress is defined as values > 310 FORT U. Results: No differences between post-exercise level of ROS for hyperoxic (259.7 ± 29.8 FORT U) and hypoxic (283.6 ± 56.5 FORT U) trial were obtained (P = 0.28; effect size = 0.53). Pre- to post-exercise FORT values were the same with hyperoxic (262.3 ± 32.2 to 259.7 ± 29.8 FORT U; P = 0.69) and with hypoxic (268.4 ± 48.4 to 283.6 ± 56.5 FORT U; P = 0.21) recovery. Discussion: Hyperoxic recovery appeared to have no additional oxidative risk for athletes performing 3 x 3-min maximal interval workouts at moderate altitude compared to hypoxic recovery. Furthermore, with hyperoxic recovery FORT levels were for all athletes at all time-points below the normal range for healthy individuals (< 310 FORT U). However, it remains unclear whether a longer period of exposure to hyperoxic air during exercise may enhance ROS production and could lead to oxidative damage.